Ousting the Cypriot Ethnarch: President Makarios’ Struggle against the Greek Junta, Cypriot Bishops, and Terrorism - Şevki Kıralp (MDPI AG, 2021)
This study examined the politics and political involvements of the Orthodox Church of Cyprus in the early postcolonial era, with a special focus on the ecclesiastical coup that aimed for the ouster of Archbishop Makarios III, who was also the President of the Republic of Cyprus from 1960 to 1977. The findings indicate that the Greek junta, Greek Cypriot terrorists, and the three bishops of the Orthodox Church of Cyprus joined forces to oust Makarios by forcing him to resign his presidency. These actors were displeased with Makarios because he tolerated Cypriot communism, refused to follow Athens’ manipulations in Cypriot politics, and promoted Cyprus’ independence by abandoning the pro-Enosis (unification of Cyprus with Greece) political line. The Greek junta tried to dictate policies to Makarios and asked him to resign as he refused to obey. Greek Cypriot terrorists engaged in violence to destabilize the island and oust Makarios. The three bishops summoned the Holy Synod and defrocked the Archbishop as he refused to resign his presidency. Importantly, this research came across with strong indicators that the Greek junta tried to utilize religion in trying to oust the Cypriot ethnarch as the three bishops, immediately after the junta’s failure to oust Makarios in 1972, asked him to resign his presidency. While his rivals failed to oust Makarios, at least until 1974, he called for an international synod and defrocked the three bishops. He managed to retain both posts until the end of his life.